Agility as a Dominant Predictor of Basketball Dribbling Skills: Evidence from Vocational High School Students - Muhammad Ridho; Mutiara Syabillah; Mawardinur Mawardinur; Swandy Pardomuan (Joska: Jurnal Isori Kampar, 2024)
Objectives: Penelitian ini bertujuan untuk menganalisis secara komprehensif dampak implementasi kebijakan Merdeka Belajar terhadap kualitas pendidikan jasmani di Indonesia melalui studi literatur sistematis. Methods: The study involved 60 male students (age 15-17 years) from State Vocational High School 8 Medan. Speed was measured using a 30-meter sprint test, agility through the Illinois Agility Test, and dribbling skills via the Control Dribble Test. Statistical analysis included Pearson correlation and multiple regression analysis, with significance set at p < 0.05. Results: The analysis revealed significant correlations between speed and dribbling skills (r = -0.68, p < 0.05) and between agility and dribbling skills (r = -0.72, p < 0.05). Multiple regression analysis showed that speed and agility collectively explained 64% of the variance in dribbling performance (R² = 0.64), with agility contributing 45.3% and speed contributing 18.7%. Conclusion: Agility emerged as the dominant factor in basketball dribbling performance, contributing significantly more than speed. While both components are important, training programs should emphasize agility development while maintaining appropriate speed training. These findings suggest the need for integrated training approaches that prioritize agility development in basketball skill enhancement programs.